The influence of corporate social responsibility activities on customer value co-creation: the mediating role of relationship marketing orientation - Mubushar, Muhammad; Norizan, Jaafar; Rossazana, Ab Rahim (Emerald Publishing Limited, 2020)
Purpose – This paper aims to investigate the impact of external stakeholders-related corporate social responsibility (CSR) activities (local community and suppliers) on customer value co-creation behavior. This study also aims to examine the mediating role of relationship marketing orientation (RMO) on the relationship of CSR activities and customer value co-creation behavior. Design/methodology/approach – The main problem of dichotomy between customers and the management was existing in banking sector so that’s why through purposive sampling, banking customers were selected for data collection through a self-administered questionnaire. Structural equation modeling was used to test the proposed hypotheses. Findings – The present study found that both local community-related and supplier-related CSR activities have a positive impact on customer value co-creation behavior. Relationship marketing orientation mediates between the link of CSR activities and customer value co-creation behavior. The strength of RMO in CSR supplier and customer value co-creation behavior is found to be more dominant. Research limitations/implications – This study is restricted to one country under-investigation; therefore, it can be replicated with a larger and more geographically diverse sample.